Failure to Thrive—An Analysis of 83 Cases - Riley, R. L. (1968)
The case histories of 83 children admitted to the hospital with a diagnosis only of failure to thrive were examined. In twenty-six cases there was evidence of maternal deprivation as a factor. Forty patients were found to have significant organic diseases as a possible or probable cause or contributing influence. Twenty-six were found to have some degree of mental retardation, either documented or suspected, but in nearly all of them there were associated factors presumably responsible, at least in part, for failure to thrive. Several children had birth weight less than 2,500 grams, but no child was thought to grow poorly because of prematurity alone. Congenital anomalies such as cleft palate and other problems leading to feeding difficulties were not unusual. In any case of persistent failure of an infant to gain adequately in weight and length, in which the cause is not evident, the child should be admitted to a hospital to determine response in a new environment. Also an adequate social history should be sought and siblings more closely evaluated; and careful study should be made of the renal, gastro-intestinal, cardiac, pulmonary and central nervous systems, even if there are no symptoms or signs referable to these systems.